ANALISIS KESULITAN SISWA SMA DALAM PENYELESAIAN SOAL HOTS PADA MATERI USAHA DAN ENERGI DI PEKANBARU - Nada Intan Shabirah; Z Zulirfan Z Zulirfan; Azhar Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims is to describe the difficulties experienced by students of SMAN 4 Pekanbaru and explain the factors causing difficulties in solving HOTS questions based on Heller Stages indicators. This research uses survey research methods. The research procedure used is preparing instruments, determining population and samples, taking research data, analyzing research data (descriptive analysis), and summarizing research results. The instrument used in this study is a matter of such diagnostic tests HOTS essay about work and energy as much as 5 questions. Other instruments in the form of a questionnaire, this questionnaire consisted of 12 statements and compiled based on indicators of the Heller stages and learning material about work and energy. The subjects of this study were 7 classes taken from 3 classes using stratified random sampling technique. The results showed that among all types of Heller stages that had the highest percentage of difficulty values were the 1st Heller stages, which illustrated a sketch of the problem with a percentage of 47.3% included in the difficult category. Based on the questionnaire, students made the most mistakes at the 3rd Heller stages, namely writing a formula that was used with a percentage value of agreeing to 92%.Key Words: Student’s difficulties, Problem solving, HOTS questions in physic, Heller Stages,Work and energy.